Measures to evaluate quality of care in head and neck cancer: Results of a Delphi study. Issue 28 (1st October 2022) - Garcia-Foncillas, Jesus; Cruz Hernandez, Juan Jesus; Arrazubi, Virginia; Escobar, Yolanda; García Castaño, Almudena; Grau, Juan J.; Iglesias, Lara; Lambea, Julio; Perez Segura, Pedro; Antón, Cristina; Caballero, Fernando; Campos, Francisco J.; et al.
Abstract : 358 Background: Currently, no specific measures are used in Spain to evaluate quality of care in head and neck cancer, and programs such as the Quality Oncology Practice Initiative developed by the American Society of Clinical Oncology does not include head-and-neck-specific measures. Methods: A systematic literature review was carried out to identify measures useful for evaluating quality of care in head and neck cancer. A scientific committee, comprising 9 medical oncologists specialized in head and neck cancer, reviewed the literature findings and developed measures to be evaluated in a 2-step Delphi method. Experts in head and neck cancer practicing in Spain—specialized in medical oncology, radiotherapy oncology, maxillofacial surgery, pathology or otorhinolaryngology—participated in the Delphi, scoring the appropriateness of the measures using a 9-point Likert scale (1, extremely inappropriate; 9, extremely appropriate). Consensus was defined as at least two-thirds of Delphi respondents selecting a score sub-category (1–3, 4–6, or 7–9) that encompassed the median score of the group. Results: Out of the 833 documents found with the literature review, 20 were selected from to identify measures of interest. Fifty measures, covering diagnosis (13), treatment (28), follow-up (5), and outcome (4), were evaluated with the Delphi method. The 52 Delphi participants reached consensus on the appropriateness of using all 50 measures to evaluate the quality of care in head and neck cancer. Measures with lowest scores concerned re-hospitalization shortly after surgery and long hospitalization after surgery. Measures with highest scores regarded the use of imaging for follow-up, a histology study prior to treatment, and complete resection of the tumor. The scientific committee then selected 29 measures based on their applicability and cost-effectiveness and developed index cards with definitions, formulas, acceptable level of attainment, and rationale for their use in clinical practice. Conclusions: The goal of this study was to develop measures to evaluate and improve the quality of care in head and neck cancer. These results show unanimous consensus from a group of experts on the proposed measures for diagnosis, treatment, follow-up, and outcome. The index cards developed with measures are easy to follow and their use could improve quality of care.